Low-intensity sprint training with blood flow restriction improves 100-m dash - Behringer, M.; Behlau, D.; Montag, J. C. K.; McCourt, M. L.; Mester, J. (The Journal of Strength and Conditioning Research, 2017)
We investigated the effects of practical blood flow restriction (pBFR) of leg muscles during sprint training on the 100-m dash time in well-trained sport students. Participants performed 6 × 100-m sprints at 60-70% of their maximal 100-m sprinting speed twice a week for 6 weeks, either with (intervention group [IG]; n = 12) or without pBFR (control group [CG]; n = 12). The 100-m dash time significantly decreased more in the IG (-0.38 ± 0.24 seconds) than in the CG (-0.16 ± 0.17 seconds). The muscle thickness of the rectus femoris increased only in the IG, whereas no group-by-time interactions were found for the muscle thickness of the biceps femoris and the biceps brachii. The maximal isometric force, measured using a leg press, did not change in either group. However, the rate of force development improved in the IG. Growth hormone, testosterone, insulin-like growth factor 1, and cortisol concentrations did not significantly differ between both groups at any measurement time point (pre, 1 minute, 20 minutes, 120 minutes, and 24 hours after the 6 all-out sprints of the first training session). The muscle damage marker h-FABP increased significantly more in the CG than in the IG. The pBFR improved the 100-m dash time significantly more than low-intensity sprint interval training alone. Other noted benefits of training with pBFR were a decreased level of muscle damage, a greater increase of the rectus femoris muscle thickness, and a higher rate of force development. However, the tested hormones were unable to explain the additional beneficial effects.